Online outsourcing and the future of work. Issue 3 (15th August 2019) - Thomas, Tessa A.; Ray, Korok
Abstract : Purpose: The purpose of this paper is to provide an argument supporting the growth of online outsourcing, which will exponentially increase in the coming years with the spread of internet availability to the less-developed regions of the world. In addition, this paper stresses the role of human decision-making in fostering this growth, rather than promoting inhibitory policies because of nationalism or fear of change. Design/methodology/approach: First, globalization and the three "waves" of outsourcing are discussed. Next, the economic principles guiding online outsourcing (disintermediation, the rise of global internet connectivity and the benefits of output-based pay over input-based pay) are discussed. After explaining how artificial intelligence will complement rather than replace human laborers, a case study and evidence are provided. Then, suggestions for government policies going forward, including skill development and education are provided. Finally, the debate that will inevitably emerge regarding online worker benefits is introduced. Findings: Evidence points toward the growth of online outsourcing and the resulting increased efficiency and gains through this type of trade. The increase in freelance workers and their earnings, the investments of Google and Facebook to develop internet capabilities in less-developed regions and the reducing costs of technology (such as laptops) provide support for this argument (Elance, 2013 ; Forbes, 2014;Pofeldt, 2015 ). Finally, a case study provides evidence illustrating how individuals may gain from these advances. Originality/value: This paper contributes to the literature by providing a compelling argument for the upcoming transition to increased efficiency in work through online outsourcing. Technological advances will allow the modern worker to delegate his/her mundane tasks so that he/she is free to focus on more pressing issues. This shift will multiply the domestic and foreign labor markets, creating opportunities that have not been available to this point. As this transition is not inevitable, this paper further outlines suggestions for policymakers to ensure maximized gains in the future.